Aphonopelma braunshausenii Tesmoingt, 1996 is a nomen dubium, with review of some historic morphological characters ineffective at species delineation (Araneae: Theraphosidae) - Sherwood, Danniella (Zootaxa, 2019)
Aphonopelma braunshausenii Tesmoingt, 1996 is regarded as a nomen dubium due to the lack of a deposited holotype, an inadequate description which gives no stable taxonomic features to differentiate it from any other species and the absence of an exact type locality. The instability of some morphological characters which were given weight for species delineation in many earlier works is discussed and illustrated.